2013
DOI: 10.1097/hjh.0b013e32835eb5a9
|View full text |Cite
|
Sign up to set email alerts
|

The renal angiotensin system does not reveal its secrets with a cross-sectional analysis of urinary angiotensinogen levels

Abstract: The renal angiotensin system does not reveal its secrets with a cross-sectional analysis of urinary angiotensinogen levels Branko Braam I have been puzzled by the findings and the interpretation thereof presented by Zou et al.[1] in the Journal. Briefly, they report a positive correlation between sodium excretion and urinary angiotensinogen levels. Moreover, urine angiotensinogen levels were correlated with blood pressure. We were not informed about the clinical characteristics of the patients with higher vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Others and we have previously reported that the urinary AGT excretion rate could be a marker of intrarenal RAS status in hypertension [9,16,17,18], as well as in CKD [7,19,20,21,22]. However, the effect of ARB on urinary AGT has not yet been examined in patients with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 96%
“…Others and we have previously reported that the urinary AGT excretion rate could be a marker of intrarenal RAS status in hypertension [9,16,17,18], as well as in CKD [7,19,20,21,22]. However, the effect of ARB on urinary AGT has not yet been examined in patients with metabolic syndrome.…”
Section: Introductionmentioning
confidence: 96%